A survey on occurrence of Cladosporium fulvum identifies race 0 and race 2 in tomato-growing areas of Argentina - Medina, Rocio (2015)
The presence of Cladosporium fulvum (syn. Passalora fulva), causal agent of tomato leaf mold, was confirmed in the two main greenhouseproduction areas for tomato in Argentina. Using both morphological characters and internal transcribed spacer sequencing, we confirmed the presence of physiological races of this pathogen. A diagnostic multiplex polymerase chain reaction (PCR) was also developed, using primers derived from C. fulvum avirulence (Avr) genes. In all, 20 isolates of Cladosporium spp. were obtained as monospore cultures and 12 were identified as C. fulvum. By this method, we showed that, of these 12 isolates, 5 were race 0 (carrying functional Avr2, Avr4, Avr4E, and Avr9 genes) and 7 were race 2 (lacking the Avr2 gene). Race identity was confirmed by testing their virulence on a set of tomato differentials carrying different Cf resistance genes. All Avr genes could be amplified in single or multiplex PCR using DNA isolated from in vitro grown monospore cultures but only three Avr could be amplified when genomic DNA was isolated from C. fulvum-infected necrotic leaf tissue.